Islam and the Secular State in Indonesia - Assyaukanie, Luthfi 1967- (Institute of Southeast Asian Studies, 2009)
"This is an excellent book which will have a major impact on the current debate about the relationship between Islam and politics in Indonesia. Its greatest strength is its innovative characterization of three Indonesian Muslim models of polity, as opposed to the normal two, Islamic state and secular state. Assyaukanie brilliantly delineates a third model, which he calls the Religious Democratic State, in the process greatly clarifying our understanding of the previous models, which he now proposes to label the Islamic Democratic State and the Liberal Democratic State. Another strength of the book is methodological. Each of its arguments is solidly grounded in the thoughts and actions of particular players, Indonesian Muslim thinkers and activists." - Professor R. William Liddle, Ohio State University, United States of America
Title from publisher's bibliographic system (viewed on 24 Nov 2015)
Keywords: Islam and secularism; Islam and state / Indonesia; Islam and secularism / Indonesia; Hochschulschrift